Secularity as a tool for religious indoctrination and identity formation: a case of semi-urban community in Nepal - Shurendra Ghimire (Globe, 2018)
This article presents the complexity of a secularization process that goes on in a state where Hinduism is culturally embedded and dominant. The term 'secular' is meant to indicate the state's 'dis-involvemet' in religious issues. However, Nepal faces a complex and ambivalent process of secularization. On the one hand, the state itself has encouraged diverse cultural communities to bring religious schools into practice. On the other, people of diverse communities are increasingly motivated to seek their identities via religious practices. Amid this confrontation, this ethnographic study, conducted in a single territory with diverse religious communities, organizations and schools, challenges the very dis-involvement of the state, community and individual in religious matters. In the process of practicing religious rights and constructing religious identities, religious communities have come into a competition for public support and resources. This competition not only divides the communities into indigenous versus non-indigenous forms but also compels the indigenous religions to go into redefinition and revival in order to resist the non-indigenous religions.